Determinan Minat Mahasiswa Akuntansi Mengadopsi Teknologi Blockchain dengan Perspektif Diffusion of Innovations Theory - Astiti, Komang Artrilens; Effendy, Lukman (LPPM Institut Pendidikan Nusantara Global, 2025)
Purpose: This research aims to explore the determinant factors that influence the interest of Mataram University accounting students in adopting blockchain technology using the Diffusion of Innovations Theory perspective. This research focuses on the characteristics of innovation, social and l factors that have the potential to improve the skills and innovation of accounting students. Methodology/approach: This quantitative study involved 306 students as selected respondents using purposive sampling methods. Data were collected through an online questionnaire and analyzed using SmartPLS. Results/findings: The results indicated that relative advantage, compatibility, trialability, and observability significantly influence accounting students’ interest in adopting blockchain technology, while complexity does not have a significant effect on students’ interest. Trialability emerged as the most crucial element affecting accounting students’ interest in adopting blockchain technology. Limitations: The limitations contained in this research are the limited population that only involves accounting students from Mataram University and the theoretical model in this research only uses the diffusion of innovations theory which focuses more on the process of spreading innovations in the population and may not fully explain the individual factors that influence students' personal decisions in adopting blockchain technology. Contribution: This research highlights the importance of collaboration between educational institutions and industry to support the adoption of blockchain technology in accounting education. The results of this study contribute to the literature related to the adoption of new technology in accounting education, particularly on blockchain technology.